Handbook of digital forensics of multimedia data and devices - Ho, Anthony T. S., 1958- (Hoboken : Wiley/IEEE Press, 2015)
"Focuses on the interface between digital forensics and multimedia forensics, bringing two closely related fields of forensic expertise together to identify and understand the current state-of-the-art in digital forensic investigation"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Criminal investigation -- Technological innovations; Electronics in criminal investigation; Digital forensic science